2011
DOI: 10.1068/i0396
|View full text |Cite
|
Sign up to set email alerts
|

Object Knowledge Modulates Colour Appearance

Abstract: We investigated the memory colour effect for colour diagnostic artificial objects. Since knowledge about these objects and their colours has been learned in everyday life, these stimuli allow the investigation of the influence of acquired object knowledge on colour appearance. These investigations are relevant for questions about how object and colour information in high-level vision interact as well as for research about the influence of learning and experience on perception in general. In order to identify s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
170
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(194 citation statements)
references
References 78 publications
12
170
1
Order By: Relevance
“…So recognizing that what is depicted in a black and white photograph is not grey but, say, red or yellow is an instance of recognizing C. And this can be and has been empirically studied-for more than 50 years. Here is a famous experiment (Delk and Fillenbaum 1965; see also Hansen et al 2006;Witzel et al 2011 for more recent and methodologically more rigorous studies): if we have to match the color of a picture of an orange heart to color samples, we match it differently (closer to the red end of the spectrum) from the way we match the color of a picture of some other, orange shapes. This shows that our recognition of the object in question (the heart) influences the color we experience it as having.…”
Section: The Depicted Object (C)mentioning
confidence: 99%
“…So recognizing that what is depicted in a black and white photograph is not grey but, say, red or yellow is an instance of recognizing C. And this can be and has been empirically studied-for more than 50 years. Here is a famous experiment (Delk and Fillenbaum 1965; see also Hansen et al 2006;Witzel et al 2011 for more recent and methodologically more rigorous studies): if we have to match the color of a picture of an orange heart to color samples, we match it differently (closer to the red end of the spectrum) from the way we match the color of a picture of some other, orange shapes. This shows that our recognition of the object in question (the heart) influences the color we experience it as having.…”
Section: The Depicted Object (C)mentioning
confidence: 99%
“…those depicting texture) and mostly absent for mere fruit/vegetable outline shapes (Olkonnen et al 2008). 18 However, this interpretation is easily dispelled by a more recent study (Witzel et al 2011). These studies involve artificial, human-made objects as stimuli.…”
mentioning
confidence: 71%
“…This is hardly conclusive, but as stated above, current empirical data is insufficient to determine some of the explanatory decisions here. Absent some further method of 19 In their initial study to identify colour diagnosticity for artificial objects, which was performed in Germany, Witzel et al (2011) found that some stereotypically German images were highly colour diagnostic (as measured by reaction time and accuracy of typical colour identification)-for example the orange Die Maus (a German television character), the yellow German mailbox, the yellow (German-made) UHU glue tube. But some non-German objects were not sufficiently colour diagnostic (relative to German subjects)-for example, the yellow Ferrari symbol and the red Soviet flag.…”
mentioning
confidence: 99%
“…There is other (more recent and much better) work on memory color than the flawed Delk and Fillenbaum study, e.g. Olkkonen et al 2008, Witzel et al 2011 between black and white faces, although perfectly genuine, turns out to be due to lowlevel features, not racial categories (Firestone and Scholl 2015). There is no change in how apertures look, and the contrary indication is likely a task compliance effect (Firestone and Scholl 2014 (Block 2014: 562-3).…”
Section: Thin Vs Rich: Can Rich Properties Be Presented In Experience?mentioning
confidence: 88%